Types of bacteria that cause urinary tract infection and extent resistance to antibiotics in some hospitals of Baghdad . - siber shiwk, Rheem; Ali Hameed, Farah (Al-Qadisiyah Journal of Pure Science, 2017)
We have designed this research study of the types of bacteria that cause urinary tract infections, where the disease is a most serious health problems facing large numbers of people each year. This research has included health status study (60) individuals of questionable them infected with the disease and auditors to hospital KadhimiyaTeaching Hospital, The Hospital of the AL-Shahed AL-Sadr in Sadr City,,ALl-HakimHospitalin Shula and Mahmudiya General Hospital, and diagnosed by examining urine microscope for people and record their information, such as locating housing and educational attainment, sex and age. and analyzed results are statistically and noon the females are more susceptible to the disease than males. and the educational attainment of the age and the effect of the increase or decrease the number of people infected with the disease. the individuals who live in civilian areas less infection than individuals who live in near by rural areas.